Constructing academic identity in the European higher education space: Experiences of early career educational researchers. (May 2020) - Djerasimovic, Sanja; Villani, Marialuisa
This exploratory paper presents insights from a qualitative interview-based study of the academic identity-building among a group of early career researchers working in the field of education across the European higher education space. Set against a policy background framed by the initiatives in European higher education and research policy, geared towards a production of a mobile, entrepreneurial researcher in pursuit of 'valuable' knowledge, the respondents' narratives reveal individual complexity, but also emerging patterns of professional identification. We identify the traditional academic values of creating and sharing knowledge validated by an epistemic community, and pursuing autonomy and collegiality in research, as still dominant, however, find these interacting with the demonstration of a strong proactive, entrepreneurial spirit, and a lack of institutional attachment. The narratives indicate the availability of supportive, encouraging communities as being of high significance, and contest the notions of Europeanisation and the utility of geographic mobility in researchers' identities. The paper discusses different types of academic identification driven by value orientation and social attachment that emerged from the early career researchers' interviews, alongside pervasive issues around mobility raised in most narratives, and concludes with suggestions for further study.